Synthesis and biological evaluation of allylated mono-carbonyl analogues of curcumin (MACs) as anti-cancer agents for cholangiocarcinoma. Issue 24 (15th December 2016) - Qiu, Chenyu; Hu, Yan; Wu, Ke; Yang, Ke; Wang, Nan; Ma, Yue; Zhu, Heping; Zhang, Yi; Zhou, Yunfang; Chen, Chao; Li, Shanshan; Fu, Lili; et al.
Graphical abstract: Highlights: A novel series of allylated mono-carbonyl curcumin analogues were designed and synthesized. Compound6c with potent antiproliferative and apoptotic activities were identified. Compound6c could be a lead compound as an anti-cholangiocarcinoma agent. Abstract: A series of new allylated mono-carbonyl curcumin analogues (MACs) were designed and synthesized. In vitro cytotoxic activities of allylated MACs6a –h together with previously reported analogues4a –i and7a –e, were tested against human cholangiocarcinoma cell lines including HUCCA, QBC-939 and RBE. Of all the compounds tested, 6c exhibited potent in vitro antiproliferative activity against the three tested cancer cell lines with IC50 values of 8.7, 9.3 and 8.9 μM, respectively. Cell cycle analysis showed that6c inhibited cell proliferation due to G2/M arrest. Furthermore, mechanistic studies revealed that6c dose-dependently increased the level of Bax and inhibited the expression of Bcl-2, to induce cancer cell apoptosis. Taken together, this work provides a novel series of anti-cancer candidates for the treatment of cholangiocarcinoma.